TOPOLOGIA DOS ORBITAIS MOLECULARES DE POLIENOS PARA DEDUZIR ENERGIAS RELATIVAS E AVALIAR AROMATICIDADE - Silvio Cunha (Química Nova)
A didactic alternative approach is proposed for deducing the molecular orbital topology of acyclic and cyclic polyenes and then evaluating their bonding, antibonding, and nonbonding character. The relative energies of molecular orbitals of neutral molecules and ions were described, in addition to the orbital degeneracy to cyclic conjugated polyenes, and the method deduce correctly the relative stability of polyenes. This alternative method complements the lack of explanation of a substantial number of organic chemist undergraduate textbooks in relation to orbital degeneracy in benzene and is a pedagogical approach to teach aromaticity and antiaromaticity.